TINJAUAN HUKUM PENOLAKAN PATEN TERKAIT DENGAN KEBARUAN DARI KISARAN - Nur Hasanah (VERITAS, 2019)
Intellectual property rights are related to human creativity which is the result of the work of creativity, human sense and intention. In Intellectual Property Rights that are protected is the right of the owner of Intellectual Property Rights, not the final product produced by the owner of Intellectual Property Rights. In the global economic order, Intellectual Property Rights are seen as a trade problem that includes interactions of three main aspects, namely intellectual property, commercialization and legal protection. This means that Intellectual Property Rights become important when there are intellectual works that will be commercialized so that the owners of intellectual works need formal legal protection to protect their interests in obtaining benefits from the commercialization of their intellectual work. This study explains the role of how the decision of the Patent Appeal Commission on patent applications, especially on patent applications number W00200903691 submitted by Repros Therapeutics Inc. through Intellectual Property Consultants in Indonesia who represent it (in this case AMR Partnership) with the title of the invention "Antiprogestin Dosage Regimen" and how to analyze the decision.